Seroprevalence and Endemic Status of Babesia ovis by Enzyme-Linked Immunosorbent Assay in East Azerbaijan Province, North-West of Iran - Hossein Hashemzadeh Farhang; Nafis Akbari-Shahkhosravi (Tehran University of Medical Sciences, 2024)
Background: Babesia ovis, an intraerythrocytic parasite carried by ticks and one of the most common subclinical ovine illnesses, was studied to ascertain its seroprevalence and endemic status in ram and ewe populations in East Azerbaijan Province, Iran, in lambs, yearlings, and adults of over two years of age. Methods: A total of 960 sheep from 10 cities were selected from Jan 2018 to Nov 2019. Blood samples were collected from each animal and tested for the presence of B. ovis antibodies by applying a developed enzyme-linked immunosorbent assay (ELISA) technique. Checkerboard titrations were used to determine the optimal dilution of the antigen using negative and positive control sera. To determine whether the disease is endemically stable, inoculation rates for each age group were also calculated. Correlation coefficients were calculated between age and infection rates and also between age and inoculation rates. Results: The results revealed an average infection rate of 49.4% in East Azerbaijan Province. There was a positive correlation between the age of animals and susceptibility to infection except for lambs and yearlings, whereas there was no meaningful difference in exposure to B. ovis between rams and ewes. The negative correlation between age and inoculation rates indicates increased disease instability with age. Inoculation rate results revealed the endemically instable status of B. ovis in the studied area. Conclusion: High prevalence rates and endemically instable status of the disease suggest demand for vaccine development and implementation of appropriate control measures for ovine babesiosis to mitigate the associated economic losses.